Peran ganda perempuan: menemukan keseimbangan karir dan keluarga di era revolusi industri 4.0 dan era society 5.0 - Ameilia, Mufidatul (Maliki Interdisciplinary Journal, 2025)
The purpose of writing this article is to understand how the dual role of women and the contribution of women today to create a balance between career and family in the era of the Industrial Revolution 4.0 and society 5.0. Her presence should be used as well as possible, because this era offers convenience for women to carry out their roles. The method used in this study is a comparative approach, where the researcher discusses how technological advances in this era will present solutions related to how to balance the dual role of women. The result of this research is to provide awareness for women out there to play a role in building civilization through examples of inspiring figures and various achievements. In addition, to provide education that the position of women should not be underestimated, awareness of gender equality between men and women is needed in this regard.